Pharmacovigilance of herbal medicine in two public health centers of Yogyakarta - Dyah Ariani Perwitasari; Mustika Muthaharah; Nur Mahdi; I Nyoman Kertia (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Background : The use of herbal medicine in Indonesia is getting increase. People try to keep their health or to prevent some diseases using herbal medicines. However, the safety of herbal medicine used in community has not known yet, due to the limited data and believe that herbal medicine is safer than modern medicines. Objective : This study was aimed to understand the safety of herbal medicine used in Yogyakarta. Methods : We used retrospective data of patients who were prescribed herbal medicine by the physicians in two public health centers in Yogyakarta. We searched for the patients identity in the medical records then we did the interview and gave questionnaire to the patients at their homes. The Adverse Drug Reaction was identified using Naranjo algorithm. This study has been approved by ethical committee of Universitas Ahmad Dahlan, Yogyakarta. Results : We identified 47 patients prescribed with herbal medicine as complementary treatment. There are 10 patients (21.3%) experienced ADR. The category of ADR are: probable (7 patients) and possible (3 patients). Tensigard is the most phytopharmaca cause pruritus in this study. Conclusion : Around 20% patients experienced ADR due to the herbal medicine prescription in complementary treatment. Thus, the study of pharmacovigilance is needed to be conducted in bigger sample size and cohort design to understand the safety profile of herbal medicine used.